Anatomy of cluster development in China: The case of health biotech clusters - Marcus Conlé; Markus Taube (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2010)
Focussing on China's health biotech clusters the study explores the anatomy of interaction in as well as between various clusters. While the literature has identified the existence of a dense network of durable interactions among firms and between firms and academia at a particular location as one of the most important prerequisites for well-performing clusters, we show that network ties extending beyond regional boundaries are equally valuable for the innovative capacity of China's biotech firms. Analysing the demographic process of cluster emergence we show that there exist different types of biotech clusters in China, which are closely linked and exchange knowledge and technology amongst each other. It appears as if further analysis of these cross-cluster links may provide important insights of how learning and innovation works in China's health biotech industry. Although China's science parks and industrial bases may on an individual basis appear to be badly structured, the organization of China's health biotech industry turns out to be substantially enhanced once these external linkages are taken into consideration.
Keywords: 330; China; health biotechnology; cluster; entrepreneurship; localization; Biotechnische Industrie; Medizin; Regionale Konzentration; Unternehmensnetzwerk; China